Diagnóstico georreferenciado do uso e ocupação do solo nas áreas de preservação permanente (APP) da sub-bacia B1, bacia do rio Cocó, Fortaleza-Ce - Araújo, Laiz Hérida Siqueira de (2012)
This research was mainly aimed at making the georeferenced diagnosis of the use and occupation of the lands directly influenced for the Sub-Basin B1 of the great basin of the Coco River, in Fortaleza, Ceará, from the appreciation of the occupancy conditions of the APP constituents of the eight watersheds, all of that inserted in the urban environment and too much impacted by urbanization that has occurred in recent decades in Fortaleza. In this sense, it was realized a documentary search in public agencies and through the internet, involving legislation, reports, statements and cartographic records of the studied area, besides several field visits, to consolidate the information. However, the scarcity of data has generated the need to prepare thematic maps that make possible the diagnosis. This way, based on the Forest Code deliberations, in Resolutions nº 303/02 and 369/06 from Conama, and the Municipal Decree nº 12.450/08, it was elaborated georeferenced maps delimiting the APP, using as reference orthophotos ,of flights 2004 and 2010, at UTM – zone 24S, South American Datum1969 (SAD 69) coordinate, using ArcGis, version 9.3 program. It Was verified that the municipal legislation presents more permissive than federal determinations reducing, in the most of cases, the APP of this sub-basin. In consequence of that, there is too much regular and irregular occupation of APP lands, that causes large gaps in relation to riparian vegetation. It is noteworthy that, even taking part of the resolution n 369/06 from Conama, there is an intense surface sealing that potentiates the vulnerability of environmental degradation in this area. In this scenario, it becomes evident the predatory use of these natural resources restricting the multiple uses and actions that promote sustainable development. This way, it is proposed recovery actions and protection of these ecosystems trying to rebalance them, since they have great importance in the landscape and improving the quality of life. Finally, it is suggested a greater commitment of public agencies to facilitate the accessibility of information about environmental issues in the city, so that, there is greater interaction between academia and public administration, generating information that can support decision making.